Pengaruh Penerapan Model Pembelajaran Time Token terhadap Motivasi Belajar Siswa Kelas V pada Pembelajaran Tematik di Sekolah Dasar Negeri 3 Ciherang - Enjen Jaenal Mutaqin; Neng Liya Yuliyanegsih (Edu Berkah Khatulistiwa, 2023)
The purpose of this study was to determine the effect of applying the time token learning model on student learning motivation: (1) How to apply the time token learning model for class v students of Elementary School Negri 3 Ciherang? (2) How is the learning motivation before and after the implementation of the time token learning model on students' learning motivation in thematic learning class v of Elementary School 3 Ciherang? (3) Is there a significant effect of the time token learning model on learning motivation in thematic learning class v of Elementary School 3 Ciherang? This study uses a type of quantitative research with an experimental method with a pre-experimental research design type one group pretest-posttest design. In this study, the population was all children at SD Negeri 3 Ciherang, Kadugede District, for the research sample, namely all students in class V, totaling 32 students. The average result of the pretest was 71.87, after the pretest was carried out then given treatment using the time token learning model to increase student learning motivation in thematic learning, during the treatment there was an increase as seen from the posttest results where the average was 79, 15. Based on the calculated t value of the SPPSS results of (4,593) and t table, a value of (2,036) is obtained so that tcount < ttable, then Ho is rejected, then Ha is accepted and the results are significant, namely the significant value is less than 0.05, namely sig. (0.00) < 0.05 so that Ho is rejected, then Ha is accepted, which means the use of the time token learning model affects the learning motivation of fifth grade students in thematic learning.